Microscopic failure of dendrocalamus asper (buluh betong) loaded in tension / Shahril Anuar Bahari, Mansur Ahmad and Mohd Arif Jamaludin - Bahari, Shahril Anuar; Ahmad, Mansur; Jamaludin, Mohd Arif (2004)
Microscopic failure in relation to strength of Dendrocalamus asper (Buluh Betong) loaded in tension parallel to grain at different culm portion and between internodes and nodes were investigated. The microscopic failure for internodes when loaded in tension occurred primarily at parenchyma region especially at radial direction. The vascular bundles in internodes are stronger compared to parenchyma and are reinforcing the structure in bamboo. The long and parallel orientation of fibers ill internodes increased the resistance of vascular bundles to tension load and this led to the higher tension strength in internodes. At tangential direction for internodes, the failure occurred on both vascular bundles and parenchyma region. On the other hand, the microscopic failure for nodes occurred at both vascular bundles and parenchyma cells on both directions. This might be due to the uneven orientation of vascular bundles. The short forked and crossed fibers in node had also reduced the strength and led to the lower tension strength in nodes. As a comparison, there is an increased in tension strength properties such as Maximum Tension Stress, Tension Stress at Proportional Limit and Tension Modulus of Elasticity from bottom to top portion due to the increment of fibers amount at the respective portion. Specimens with node are lower in tension strength due to the present of uneven orientation of vascular bundles as well as short, forked and crossed fibers, compared to the even orientation of vascular bundles, long and parallel orientation of fibers in internodes.